FFRCT and Invasive Coronary Angiography – assessing concordance in an unselected UK real world population. (14th October 2021) - Murphy, D; Graby, J; McKenzie, D; Kandan, S R; Carson, K; Lowe, R; Khavandi, A; Hudson, B; Rodrigues, J
Abstract: Background/Introduction: CT coronary angiography (CTCA) Fractional Flow Reserve (FFRCT) is a key investigation in chronic coronary syndrome (CCS) guidelines. FFR calculated from CTCA may help improve CTCA specificity for flow limiting disease, preventing unnecessary invasive coronary angiography (ICA). Purpose: To (1) assess the treatment planning potential of FFRCT by determining the concordance of FFRCT with an ICA +/− invasive physiological assessment for the detection of flow limiting CAD in a real world NHS setting and (2) concordance sub-analysis of concordance of invasive iFR and FFRCT. Methods: A single-centre retrospective analysis of a prospectively maintained clinical CTCA database. We identified patients with CCS who had CTCA FFRCT and subsequent ICA from August 2018 to January 2021. Concordance was assessed on a per patient and per vessel basis (major epicardial vessels: left main stem [LMS], left anterior descending artery [LAD], circumflex [LCx], right coronary artery [RCA]). Two non-invasive ischaemia thresholds were examined an FFRCT ≤0.8 and <0.75 (2 cm distal to stenosis). This was compared to a clinical ICA assessment where a flow limiting lesion was defined as a stenosis >70% (or >50% in the LMS) and/or an end vessel iFR ≤0.89 / FFR ≤0.8. All vessels that underwent an iFR, at the interventionists discretion, were then assessed relative to their end-vessel FFRCT. Results: 565 patients had a CTCA with FFRCT and 164 patients had a subsequent ICA and were suitable for analysis. On a per patient basis 69% of those referred to ICA with an FFRCT ≤0.8 of at least one major epicardial vessel had any flow limiting CAD at ICA. With an FFRCT <0.75 this was 73%. Table 1 illustrates the per vessel concordance. A total of 120 vessels were included in the iFR subsection analysis. The mean FFRCT was 0.71 (±0.13) and mean iFR was 0.89 (±0.1). Accuracy was 54% (95% CI 45–63%) with a sensitivity of 89% (95% CI 76–96%), specificity 32% (95% CI 22–44%), positive predictive value 45% (95% CI 40–50%) and negative predictive value of 83% (95% CI 66–92%). A Pearson's correlation coefficient of 0.23 was found. Conclusion: This study demonstrated that the negative predictive value of FFRCT was excellent, including importantly for LMS analysis. The specificity on a per vessel basis was good with the exception of the LAD assessment. This may have implications for interventional planning with this imaging modality. FFRCT correlated poorly with invasive iFR in this subsection analysis although selection bias may be contributing. There remains a significant proportion of patients referred for an ICA where no flow limiting CAD is found. FUNDunding Acknowledgement: Type of funding sources: None.